Virological response and resistance profile in highly treatment‐experienced HIV‐1‐infected patients switching to dolutegravir plus boosted darunavir in clinical practice. Issue 6 (21st January 2021) - Armenia, Daniele; Bouba, Yagai; Gagliardini, Roberta; Fabeni, Lavinia; Borghi, Vanni; Berno, Giulia; Vergori, Alessandra; Cicalini, Stefania; Mussini, Cristina; Antinori, Andrea; Ceccherini‐Silberstein, Francesca; Perno, Carlo Federico; et al.
Abstract : Objectives: We evaluated the virological response and resistance profile in combined antiretroviral therapy (cART)‐experienced HIV‐1‐infected patients starting a dual therapy with dolutegravir (DTG) and boosted darunavir (bDRV) for the first time. Methods: Survival analyses were used to evaluate virological success (VS) and virological rebound (VR) in viraemic and virologically suppressed patients, respectively. Major resistance mutations (MRMs) and genotypic susceptibility score (GSS) were evaluated at baseline and after switch. Results: Overall, 130 patients [62 (47.7%) viraemic; 68 (52.3%) virologically suppressed] were retrospectively analysed. At the moment of switch, 81.5% accumulated one or more MRM [protease inhibitor (PI), 35.7%; nucleoside(t)ide reverse transcriptase inhibitor (NRTI), 77.5%; non‐NRTI, 69.0%; integrase inhibitor (INI), 10.1%), but 77.7% harboured strains fully susceptible to DTG + bDRV. In viraemic patients, the overall probability of VS by 12 months of treatment was 91.7%. In virologically suppressed patients, the overall probability of VR was 10.5% by 24 months after therapy start. Patients with previous time under virological suppression ≤ 6 months showed a higher VR probability compared with others (37.5% vs . 6.7%, P < 0.002). Among 13 non‐responding patients for whom a genotypic resistance test result at failure was available, only two (15.4%) accumulated further resistance in integrase (Y143C/H/R; S147G and N155H) and protease (V32I, L33F, I54L). Conclusions: In highly treatment‐experienced patients, the use of dual therapy based on DTG + bDRV appears to be a very good regimen for switch therapy, with a high rate of virological control in both viraemic and virologically suppressed patients. Among non‐responding patients, the selection of further resistance is a rare event.